2013
DOI: 10.1016/j.electacta.2013.07.129
|View full text |Cite
|
Sign up to set email alerts
|

Laccase biosensor based on screen-printed electrode modified with thionine–carbon black nanocomposite, for Bisphenol A detection

Abstract: a b s t r a c tThe relevance of Bisphenol A (BPA) in human health is well-known. For this reason we designed and developed a biosensor based on a bionanocomposite (laccase-thionine-carbon black)-modified screenprinted electrode. Thionine, a commercially available dye, was used as electrochemical mediator coupled with a nanostructured carbon black. By means of cyclic voltammetry, the interaction of thionine adsorbed on modified screen printed electrode with laccase/BPA reaction products has been studied. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
44
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(52 citation statements)
references
References 51 publications
6
44
1
1
Order By: Relevance
“…The analytical performances of the CuMOF-Tyr-Chit/GCE biosensor were compared with other enzyme biosensors that have been developed previously (Table 1). From Table 1, it can be seen that the sensitivity of the Cu-MOF based biosensor is higher than that of the graphene (Wu et al, 2012a), carbon nanotubes (Mita et al, 2007;Ren et al, 2011;Yin et al, 2010) or carbon-black (Portaccio et al, 2010;Portaccio et al, 2013) based biosensor. The Cu-MOF biosensor exhibits the lowest detection limit and the highest sensitivity for BPA among those biosensors.…”
Section: Amperometric Biosensing Of Bpamentioning
confidence: 83%
See 1 more Smart Citation
“…The analytical performances of the CuMOF-Tyr-Chit/GCE biosensor were compared with other enzyme biosensors that have been developed previously (Table 1). From Table 1, it can be seen that the sensitivity of the Cu-MOF based biosensor is higher than that of the graphene (Wu et al, 2012a), carbon nanotubes (Mita et al, 2007;Ren et al, 2011;Yin et al, 2010) or carbon-black (Portaccio et al, 2010;Portaccio et al, 2013) based biosensor. The Cu-MOF biosensor exhibits the lowest detection limit and the highest sensitivity for BPA among those biosensors.…”
Section: Amperometric Biosensing Of Bpamentioning
confidence: 83%
“…The good selectivity of the biosensor is attributed to the biocatalytic specificity of tyrosinase for BPA. Other potential co-existing plasticizer Portaccio et al (2013) interferences (e.g. phthalates) are not the substrate of tyrosinase, which will not interfere with the detection of BPA by tyrosinase based biosensors (Wu et al, 2012a).…”
Section: Amperometric Biosensing Of Bpamentioning
confidence: 99%
“…The determination of the content of urea in milk samples, phenolic compounds in olive oil samples, and bisphenol A in tomato juice samples was interesting applications in the scenario of food analysis investigated by Laurinavicius et al [87], Nadifiyine et al [78], and Cammarota et al [77], respectively. In the work proposed by Laurinavicius et al [87], a CB paste electrode was modified with a flexible membrane based on terylene precoated with polyvinyl alcohol (PVA-T) containing the immobilized urease enzyme.…”
Section: Biosensors Based On Nanostructured Carbon Blackmentioning
confidence: 99%
“…The applicability of the proposed biosensor was proved from the analysis of different olive oils with results statistically similar to those obtained by using a comparative Folin-Ciocalteu spectrophotometric method. In the work reported by Cammarota et al [77], the bisphenol A was determined using a biosensor based on screen-printed electrodes (SPEs) modified with a bionanocomposite of laccase, thionine, and CB. In a previous work, the same research group reported a short communication paper demonstrating the remarkable analytical potentialities of SPEs modified with CB for the sensing of phenolic compounds (catechol, caffeic acid, gallic acid, and tyrosol) [58].…”
Section: Biosensors Based On Nanostructured Carbon Blackmentioning
confidence: 99%
“…Meanwhile, as BPA is an electrochemically-active molecule, the electrochemical method is considered to be a better choice in the on-site determination for its simplicity, sensitivity and selectivity. Different materials were reported for the electrochemical detection of BPA, including metal composites, 35,36 43 ). However, the sustainable and rich-doped carbon materials derived from biomass have not been reported for the electrodetermination of BPA yet.…”
mentioning
confidence: 99%